Interictal spike connectivity in human epileptic neocortex. Issue 2 (February 2019) - Maharathi, Biswajit; Wlodarski, Richard; Bagla, Shruti; Asano, Eishi; Hua, Jing; Patton, James; Loeb, Jeffrey A.
Highlights: Interictal spike propagation patterns in human neocortex are highly consistent. High spiking regions are rarely the spike network initiators. The central sulcus acts as an anatomical barrier to spike propagation. Abstract: Objective: Interictal spikes are a biomarker of epilepsy, yet their precise roles are poorly understood. Using long-term neocortical recordings from epileptic patients, we investigated the spatial-temporal propagation patterns of interictal spiking. Methods: Interictal spikes were detected in 10 epileptic patients. Short time direct directed transfer function was used to map the spatial-temporal patterns of interictal spike onset and propagation across different cortical topographies. Results: Each patient had unique interictal spike propagation pattern that was highly consistent across times, regardless of the frequency band. High spiking brain regions were often not spike onset regions. We observed frequent spike propagations to shorter distances and that the central sulcus forms a strong barrier to spike propagation. Spike onset and seizure onset seemed to be distinct networks in most cases. Conclusions: Patients in epilepsy have distinct and unique network of causal propagation pattern which are very consistent revealing the underlying epileptic network. Although spike are epileptic biomarkers, spike origin and seizure onset seems to be distinct in most cases. Significance: Understanding patterns of interictal spike propagation could lead to the identification patient-specific epileptic networks amenable to surgical or other treatments.